STUDY ON THE PERCEPTION OF LUXURY VALUES, CONSUMER KNOWLEDGE, AND PERSONALITY: THEIR INFLUENCE ON THE INTENTION TO PURCHASE LUXURY FASHION PRODUCTS - Dieni, Lidya; Hartoyo, Hartoyo; Yuliati, Lilik Noor (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The intention of this paper is to investigate: (1) The effect of luxury value perceptions, consumer knowledge, and consumer personality on luxury product consumption. (2) The direct impact of luxury value perceptions, consumer knowledge, and personality on purchase intention, both independently and in the extended Theory of Planned Behavior framework (including attitude toward behavior, subjective norms, and perceived behavioral control). (3) Examine the managerial implications, particularly for the luxury goods industry. This research employs a causative research design, targeting the population of luxury customers in Greater Jakarta (Jabodetabek). The total sample for this study consisted of 180 participants who completed a questionnaire. The research results indicate that out of 15 hypotheses, three were rejected. Luxury value perceptions, consumer knowledge, and personality demonstrated a significant direct influence on purchase intention. However, no indirect effect was observed between certain personality variables and consumer knowledge when mediated by intervening variables. Keywords: Consumer Knowledge, Extended Theory of Planned Behavior, Luxury Value Perceptions, Personality, Purchase Intention